2023
DOI: 10.22541/au.167725982.25474227/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The aflatoxin B1-induced imidazole ring-opened guanine adduct: high mutagenic potential that is minimally affected by sequence context

Abstract: Consumption of foods contaminated with aflatoxin B (AFB) is a recognized risk factor for developing hepatocellular carcinomas (HCCs). The mutational signature of AFB is characterized by high frequency G > T transversions in a limited subset of trinucleotide sequences. The 8,9-dihydro-8-(2,6-diamino-4-oxo-3,4-dihydropyrimid-5-yl-formamido)-9-hydroxyaflatoxin B (AFB-FapyGua) has been implicated as the primary DNA lesion responsible for AFB-induced mutations. This study evaluated the mutagenic potential of AFB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…In addition, pol η and pol κ have the potential to contribute to mutagenic bypass of both the initial N7-dG and Fapy lesions ( 33 , 64 ). Consistent with an extremely error-prone bypass of AFB 1 -induced adducts observed in vitro , the biological consequences of blocked replication and subsequent translesion synthesis past these lesions are high frequency SBS, predominantly G > T transversions ( 33 , 34 , 64 ). Although these spectra strongly correlate with the mutagenic outcome of AFB 1 exposure ( 12 , 14–17 , 30 , 62 ), they have been shown to be only minimally modulated by sequence context.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In addition, pol η and pol κ have the potential to contribute to mutagenic bypass of both the initial N7-dG and Fapy lesions ( 33 , 64 ). Consistent with an extremely error-prone bypass of AFB 1 -induced adducts observed in vitro , the biological consequences of blocked replication and subsequent translesion synthesis past these lesions are high frequency SBS, predominantly G > T transversions ( 33 , 34 , 64 ). Although these spectra strongly correlate with the mutagenic outcome of AFB 1 exposure ( 12 , 14–17 , 30 , 62 ), they have been shown to be only minimally modulated by sequence context.…”
Section: Discussionmentioning
confidence: 54%
“…The AFB 1 -Fapy-dG lesion is persistent in vivo ( 25 , 28–32 ). The persistence, along with the known potential to cause high frequency base substitutions (80–90%), predominated by G > T transversions ( 33 , 34 ) implicate AFB 1 -Fapy-dG as a major contributor to AFB 1 -induced mutagenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This SI is to promote recent findings and advances on genome integrity mechanisms with emphasis on their importance for basic and environmental health sciences. This SI includes two research articles, one brief communication, and four reviews (Hoag et al, 2024; Hua & Sweasy, 2024; Hussen et al, 2024; Minko et al, 2024; Sobol, 2024; Stroik et al, 2024; Wilson & Wyrick, 2024). The findings and perspectives from this SI may help to better understand how DNA damage and DNA repair mechanisms can provide novel insights into environmentally‐induced human disease such as cancer.…”
mentioning
confidence: 99%
“…In a brief communication, the Lloyd and Stone laboratories reported that guanine adducts from dietary exposure to aflatoxin B1 (AFB1) can lead to high mutagenic G > T transversions and other base substitutions in a trinucleotide‐sequence‐independent manner (Minko et al, 2024). AFB1 can cause the single base substitution mutation signature SBS 24, and represents a significant risk factor for cancer development (Alexandrov et al, 2020; McCullough & Lloyd, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation